Ultrasonographic measurement of optic nerve sheath diameter as a bedside tool in critical care unit to identify raised intra cranial pressures - Nasir Jeelani Wani (National Scientific Medical Center, 2022)
Aim: Raised intracranial pressure is a common problem in critical care unit and is associated with worse outcome. Several methods have been used to investigate for elevated intracranial pressure (ICP). Here usefulness of optic ultrasound as a bedside tool for assessment of raised ICP in critical care setting was studied. Material and methods: A prospective study was carried out in Intensive Care Unit (ICU) of tertiary care hospital for a period of 12 months. Patients admitted in ICU during the period of study and who were at the risk of development of raised ICP and needed CT scan for diagnosis were part of the study. 115 patients were included. The optic nerve sheath was identified on ultrasound, and optic nerve sheath diameter (ONSD) was measured 3 mm posterior to the retina. A mean ONSD value of >0.5 cm was taken as positive. CT scan was done immediately afterwards to find any signs of raised ICP. Results: The mean age of participants was 42.3±10 years with majority of them male (61.7%). The number of cases diagnosed as raised ICP with optic ultrasound was 36 (31.3%) and with CT scan 33 (28.7%) cases. The calculated sensitivity and specificity of optic ultrasound in detection of raised ICP is 100.0% (95% CI: 89.4-100.0) and 96.5% (95% CI: 90.0-99.3) respectively with accuracy of 97.5%. Conclusion: The present study revealed that ultrasonographic measurement of ONSD as a bedside tool is accurate for screening of patients with probable elevation of ICP. It has advantage of being quick, is without any complication, and patient is not exposed to radiation, besides it does not expose patient to risk of transit during transport to imaging unit as in case of CT scan.